PENGARUH KOORDINASI PIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR DINAS PENDIDIKAN KOTA SAMARINDA - Gumay, Andra Surya (PREDIKSI, 2012)
This Research target is to know what Head of coordination have an effect on to Discipline Work the Officer. The research do in Office of Sub-Regency Chief of Education Of Departement of Regency of City Samarinda Result of research indicate that the head coordination [of Part of Arranging Effort very having an effect on to officer discipline, in the meaning that discipline factor work the officer at Office of Sub-Regency Chief of Education Of Departement of Regency of City Samarinda from month to month even from year to year experience of the change mounting. This matter [is] followed also by Head Coordination which in this case function as cause variable. To increase discipline work the officer, beside factor co-ordinate the head, hence factor of[is other;dissimilar require to get the attention so that discipline work the officer at office of Sub-Regency Chief of Education Of Departement Â of Regency of City Samarinda earn remain to be improved